2012
DOI: 10.1097/yct.0b013e31824532c8
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial Magnetic Stimulation (TMS) in the Treatment of Attention-Deficit/Hyperactivity Disorder in Adolescents and Young Adults

Abstract: Transcranial magnetic stimulation was found to be safe, with no serious adverse events observed in this pilot study. Improvement in symptoms was observed across the combined phases of the study, although there was no difference between the active and sham forms of TMS. Effects of clinical importance should be further assessed in larger controlled studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(60 citation statements)
references
References 0 publications
1
56
1
2
Order By: Relevance
“…rTMS was the most frequently examined NIBS modality, with 35 publications addressing the application of TMS on children and adolescents (3.0 to 17.8 years old) [3840, 4446, 52, 5557, 6467, 70, 71, 73, 7581, 83, 8594]. The duration of the interventions ranged from one day to 18 weeks, and the stimulation provided was administered in frequencies ranging from 0.3Hz to 10Hz; two studies reported priming the subject with a frequency of 6Hz before the procedure [46, 52].…”
Section: Resultsmentioning
confidence: 99%
“…rTMS was the most frequently examined NIBS modality, with 35 publications addressing the application of TMS on children and adolescents (3.0 to 17.8 years old) [3840, 4446, 52, 5557, 6467, 70, 71, 73, 7581, 83, 8594]. The duration of the interventions ranged from one day to 18 weeks, and the stimulation provided was administered in frequencies ranging from 0.3Hz to 10Hz; two studies reported priming the subject with a frequency of 6Hz before the procedure [46, 52].…”
Section: Resultsmentioning
confidence: 99%
“…TMS is continuously establishing itself as one of the “tools of the trade” in psychiatric therapeutic practice (Kammer and Spitzer, 2012) improving mental functions in: Parkinson's disease (Pascual-Leone et al, 1994), aphasia (Medina et al, 2012), motor control after stroke (Takeuchi et al, 2005), epilepsy (Nitsche and Paulus, 2009), depression (Lisanby et al, 2009; Conforto et al, 2014), schizophrenia (Levkovitz et al, 2011; Kammer and Spitzer, 2012), autism (Krause et al, 2012), chronic migraine (Conforto et al, 2014), dyslexia (Costanzo et al, 2013), neglect (Fasotti and Van Kessel, 2013), obsessive-compulsive disorder (OCD) (Mantovani et al, 2013), chronic pain (Moreno-Duarte et al, 2014), and social anxiety disorder (Paes et al, 2013). The TMS therapy applied to younger patients (children and adolescents) improves cognitive functions (Vicario and Nitsche, 2013) in: stroke affecting the motor cortex (Kirton et al, 2008), epilepsy (Fregni et al, 2005), ADHD (Weaver et al, 2012), Tourette syndrome (Le et al, 2013), autism (Baruth et al, 2010), treatment-resistant depression (Bloch et al, 2008), and medication-resistant schizophrenia (Jardri et al, 2012). …”
Section: Discussionmentioning
confidence: 99%
“…One pilot single-session, sham-controlled trial found that high-frequency rTMS over the right DLPFC improved attention difficulties in ADHD patients (Bloch et al, 2010), although another study applying 10 consecutive sessions of high-frequency rTMS over the right DLPFC did not show significant differences in attention compared to sham rTMS (Weaver et al, 2012). It should be emphasized that not only the DLPFC but also other brain areas, such as the anterior cingulate cortex and the basal ganglia, are involved (Frodl & Skokauskas, 2012); nevertheless, for non-invasive brain stimulation purposes the DLPFC might be the most accessible gateway to modulate the cortico-subcortical pathways involved in ADHD.…”
Section: Transcranial Direct Current Stimulationmentioning
confidence: 98%